Comparative in Vitro Study on the Antimicrobial Efficacy of Endodontic Sealers Against Common Oral Pathogens - Csaba Dudás; Zsuzsanna Bardocz-Veres; Anita Iulia Gyulai; Silvia Izabella Pop; Melinda Székely; Bernadette Kerekes-Máthé; Mónika Kovács (Dentistry Journal)
Background/Objectives: Microorganisms are the leading cause of infections in the root canal system, contributing to the failure of endodontic treatments. This in vitro study aimed to compare the antimicrobial effects of four different endodontic sealers: Endomethasone N (Septodont, Saint Maur-des-Fossés, France), Sealapex (Kerr Corporation, Orange, CA, USA), AH Plus Jet (Dentsply DeTrey GmbH, Konstanz, Germany), and MTA Fillapex (Angelus, Londrina, Brazil). Methods: The sealers were tested against common oral pathogens, including Enterococcus faecalis, Staphylococcus aureus, Escherichia coli, Candida albicans, and Streptococcus mutans, using the agar diffusion method. Inhibition zones were measured at 24, 48, and 72 h to assess antimicrobial efficacy. Results: The results showed that Endomethasone was the most effective sealer against all tested microorganisms, demonstrating consistent inhibition across all time intervals. MTA Fillapex also exhibited a significant antimicrobial effect, particularly against Streptococcus mutans, with its efficacy increasing over time. AH Plus Jet displayed limited effectiveness, showing significant results only against Staphylococcus aureus. Conclusions: Overall, this study confirms the superior antimicrobial performance of Endomethasone, while the other materials, particularly MTA Fillapex and Sealapex, also showed notable effects in experimental conditions. The antimicrobial activity of all materials, except AH Plus Jet, increased over the 72-h period.